Xylooligosaccharide Production from Tobacco Stalk Xylan using Xylanase Streptomyces sp. BO 3.2 - Kholis, Muhammad Nur; Yopi,; Meryandini, Anja (Makara Journal of Science, 2015)
Tobacco stalk (TS), which is one type of lignocellulosic material, has a xylan content of up to 21.9%. Lignocellulose can be used to produce xylooligosaccharides (XOs). XOs are dietary fibers that have prebiotic activity. This study aimed to produce XOs from tobacco stalk xylan using xylanase from Streptomyces sp. BO 3.2. After the TS was delignified, the xylan was extracted using the alkali method. The delignification process, which used 1% natrium hypoclorite (NaOCl), decreased the lignins from 32.93% to 18.15%. Xylan extraction was conducted using 10% natrium hydoroxide (NaOH); this extraction produced xylan of 15.53% (w/w). The xylanase produced by Streptomyces sp. BO 3.2 on a 0.5% TS medium had 5.92 U/mL of activity, with the optimum condition occurring at pH 5.5 and a temperature of 60 °C. The xylanase was stable, at temperature 4 °C and 30 °C for 120 hours. The xylanase Streptomyces sp. BO 3.2 was capable of hydrolyzing 2% TS xylan and 2% beechwood xylan during the first, third, sixth, and twelfth hours of incubation time; it also produced XOs with degrees of polymerization (DP) of 2.18 and 2.15, respectively. A Thin layer chomatography (TLC) analysis indicated that the hydrolysis products were XOs with the absence of xylose, glucose, and arabinose.